WHY DID “JAWARA” SUBANG DISTRICS FINANCIAL REPORT GET AN UNQUALIFIED OPINION? - Icih Icih (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
The flagship program of the Regent and Deputy Regent of Subang Districs in 2018-2023 is known as the 9 JAWARA Program (Jaya, Istimewa dan Sejahtera). One of the JAWARA programs is JAWARA NAGARA. One of JAWARA NAGARA's performance indicators is the acquisition of an Unqualified Opinion (WTP) from BPK RI. The audit opinion on the financial statements of Subang JAWARA Regency for the last 5 years (2018 to 2023) is Unqualified Opinion, while the previous three years (2015 to 2017) each received a Disclaimer and Qualified audit opinion, respectively. Two different conditions are interesting for research. This study aims to determine the effect of leadership commitment, regulation, code of ethics and socialization of regional financial accounting on the quality of JAWARA's financial statements, either partially or simultaneously. The population of this research is the regional apparatus organization of Subang Districs. The sampling method used is convenience sampling with 58 research samples. Hypothesis testing using multiple linear regression method. The results showed that leadership commitment, code of ethics and socialization of regional financial accounting had a significant positive effect on the quality of JAWARA's financial reports, while regulation had no effect. Simultaneously, leadership commitment, regulation, code of ethics and socialization of regional financial accounting affect the quality of JAWARA's financial reports.